2007
DOI: 10.2307/25066594
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Delivery Is Essential for Synaptic Potentiation

Abstract: Abstract. Mitochondria, as portable generators that power synaptic function, regulate the ATP supply and calcium homeostasis in the neuron. As molecular interactions within the synapses before and after the potentiation are beginning to be elucidated, the deciding moment during the tetanic stimulation that gives rise to the strengthening of the synapse remains a mystery. Here, I recorded electrically from an intact Drosophila nervous system, while simultaneously using time-lapse confocal microscopy to visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
1
30
1
1
Order By: Relevance
“…Accordingly, inhibition of mitochondrial ATP production with the complex I inhibitor rotenone interfered with synaptic accumulation of mitochondria and PTP. By contrast, boosting mitochondrial ATP production in motor axons by genetic methods increased PTP (Tong, 2007). Further illustrating the importance of synaptic localization of mitochondria in short-term synaptic plasticity, Drp1 loss-of-function mutations in Drosophila depleted mitochondria from motor nerve terminals and inhibited mobilization of the reserve pool of synaptic vesicles (Verstreken et al, 2005) (Fig.…”
Section: Mitochondrial Dynamics In Synaptic Transmission and Plasticitymentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, inhibition of mitochondrial ATP production with the complex I inhibitor rotenone interfered with synaptic accumulation of mitochondria and PTP. By contrast, boosting mitochondrial ATP production in motor axons by genetic methods increased PTP (Tong, 2007). Further illustrating the importance of synaptic localization of mitochondria in short-term synaptic plasticity, Drp1 loss-of-function mutations in Drosophila depleted mitochondria from motor nerve terminals and inhibited mobilization of the reserve pool of synaptic vesicles (Verstreken et al, 2005) (Fig.…”
Section: Mitochondrial Dynamics In Synaptic Transmission and Plasticitymentioning
confidence: 94%
“…At the Drosophila neuromuscular junction (NMJ), synaptic potentiation induced by tetanic stimulation, i.e. post-tetanic potentiation (PTP) of motor nerves increases transport of mitochondria to synaptic terminals (Tong, 2007). Accordingly, inhibition of mitochondrial ATP production with the complex I inhibitor rotenone interfered with synaptic accumulation of mitochondria and PTP.…”
Section: Mitochondrial Dynamics In Synaptic Transmission and Plasticitymentioning
confidence: 99%
“…DRP1, dynamin-related protein, is a GTPase that is a central component of the mitochondrial outer membrane fission machinery involved in regulating mitochondrial dynamics (60). It was also recently reported that pharmacological inhibition of complex I activity in Drosophila larvae significantly reduces presynaptic anterograde trafficking of mitochondria (61). Mitochondria isolated from porin-deficient flies demonstrate a significant reduction in complex I activity (Fig.…”
Section: Rev8mentioning
confidence: 95%
“…Thus, since muscle-type nicotinic acetylcholine receptors play an important role for skeletal and respiration-related muscle contraction and relaxation, these receptors are one of main targets of drugs and toxins. In previous reports, flavonoids derived from plants or tea extracts were demonstrated to affect acetylcholine release, muscle contraction and neuromuscular junction activity [14][15][16][17][18]. However, relatively little is known how flavonoids including quercetin regulate muscle-type nicotinic acetylcholine receptor channel activity.…”
Section: Non-competitive Inhibition Of α1β1δε Nicotinic Acetylcholinementioning
confidence: 99%
“…1). Flavonoids derived from plants or tea extracts affect acetylcholine release, muscle contraction or neuromuscular junction activity [14][15][16][17][18]. Especially, quercetin inhibits end-plate currents at the mouse neuromuscular junction [19].…”
Section: Introductionmentioning
confidence: 99%